ANALYSE DE LA PAUVRETÉ MULTIDIMENSIONNELLE DES MÉNAGES AGRICULTEURS ET ARTISANS MINIERS DU TERRITOIRE DE WALIKALE - Axel Munyihire Barengeke, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2024)
This article analyzes the multidimensional poverty of farming and artisanal mining households in Walikale Territory, North Kivu Province (DR Congo), based on the multidimensional approach of Alkire (2007) and Foster (2011) at two stages: identification and aggregation. Unlike the multidimensional poverty indexes developed in previous studies, mainly by UNDP and OPHI following Alkire and Foster's approach, which uses 3 dimensions made up of 10 indicators, to take into account the characteristics of the population concerned by the study, this paper uses 21 indicators grouped into 5 dimensions. In addition, it adopts a decomposition approach to the MPI according to the characteristics of the population, and in particular according to whether the respondents are farmers or miners. At the end of the analysis, the results reveal that multidimensional poverty is indeed present in the surveyed population of Walikale Territory: 81.3% of individuals surveyed are multidimensionally poor. On average, these poor individuals experience deficiencies in 48.3% of the dimensions or indicators used, i.e. in at least 2 of the 5 dimensions or in at least 10 of the 21 indicators used to measure multidimensional poverty. Also, the main measure of the Multidimensional Poverty Index, , indicates that households identified as poor suffer 39.2% of all possible total deprivations. Despite the fact that multidimensional poverty appears to be a general phenomenon in Walikale Territory, the results reveal that it is much more prevalent among farmers than among artisanal miners: 85.4% of farmers are multidimensionally poor compared with 77.3% of miners.